1981
DOI: 10.1111/j.1365-3024.1981.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of immunity to Nematospiroides dubius in mice using larvae attenuated by cobalt 60 irradiation

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…Irradiated H. polygyrus larvae given orally stimulate protection against subsequent challenge [62, 145148]. Notably, the efficacy of this irradiated larval vaccine is diminished by the coadministration of unirradiated larvae, indicating that the development of adult worms is able to inhibit development and/or expression of protective immunity against subsequent reinfection [146, 147].…”
Section: Vaccine-induced Immunitymentioning
confidence: 99%
“…Irradiated H. polygyrus larvae given orally stimulate protection against subsequent challenge [62, 145148]. Notably, the efficacy of this irradiated larval vaccine is diminished by the coadministration of unirradiated larvae, indicating that the development of adult worms is able to inhibit development and/or expression of protective immunity against subsequent reinfection [146, 147].…”
Section: Vaccine-induced Immunitymentioning
confidence: 99%
“…Moreover, mice given curative anthelminthic treatment prior to adult maturation [21], or heavily irradiated infective larvae [22] develop protective immunity to challenge infection. Hence, as well as being a source of protective antigens, immature tissue-dwelling parasites actively contribute to immunological down-regulation, and we hypothesise that in the non-immune setting they are able to deflect or disable immune mechanisms within the gut tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The breakthrough came when it was realized that adult worms not only failed to induce effective resistance in many mouse strains and appeared not to be susceptible to mucosal responses in some strains of immune mice , but actually prevented the expression of host‐protective effector mechanisms operating at the mucosal level . The larval, tissue‐dwelling stages of this parasite are in fact highly immunogenic and can induce immunity even in poor responder strains of mice , as long as the period of residence of adult worms in the gut lumen is brief, as for example after infection with irradiated infective larvae , following treatment with ivermectin, which kills the larvae in situ in the intestinal walls , or by chemotherapy immediately after their emergence from the intestinal walls 7–9 days post‐infection . It was shown that an average of just over 3 infective larvae per mouse was sufficient to generate an 84% reduction in challenge infection worm burdens in NIH mice when the immunizing larvae were killed by ivermectin on day 6 post‐infection .…”
Section: Thirty‐five Years Agomentioning
confidence: 99%